Early life programming and the risk of non-alcoholic fatty liver disease. (23rd January 2017) - Lynch, C.; Chan, C. S.; Drake, A. J.
Abstract : Non-alcoholic fatty liver disease (NAFLD) is associated with obesity, insulin resistance, type 2 diabetes and cardiovascular disease and can be considered the hepatic manifestation of the metabolic syndrome. NAFLD represents a spectrum of disease, from the relatively benign simple steatosis to the more serious non-alcoholic steatohepatitis, which can progress to liver cirrhosis, hepatocellular carcinoma and end-stage liver failure, necessitating liver transplantation. Although the increasing prevalence of NAFLD in developed countries has substantial implications for public health, many of the precise mechanisms accounting for the development and progression of NAFLD are unclear. The environment in early life is an important determinant of cardiovascular disease risk in later life and studies suggest this also extends to NAFLD. Here we review data from animal models and human studies which suggest that fetal and early life exposure to maternal under- and overnutrition, excess glucocorticoids and environmental pollutants may confer an increased susceptibility to NAFLD development and progression in offspring and that such effects may be sex-specific. We also consider studies aimed at identifying potential dietary and pharmacological interventions aimed at reducing this risk. We suggest that further human epidemiological studies are needed to ensure that data from animal models are relevant to human health.